Rhythmicity of Petrikov deposit Upper Devonian overlying bed by the core photogrammetry - Samodurov, Vladimir P.; Kutyrlo, Vitali E. (Journal of the Belarusian State University. Geography and Geology, 2019)
In the paper the rhythmicity in the stratum sequences of the gray-colored geological bed is analyzed using core photogrammetry. Upper Devonian sedimentary column of Petrikov potash deposit was studied as a subject of inquiry. Color space HSV and some color coefficients of RGB-space were used for the rock cyclicity estimation. Rock color diagrams were calculated and rhythmicity in the sedimentary column has been allocated. Stratification of the tuff marker has been studied and its usage for the rock correlation is shown. Quantitative initial data of the color parameters are the advantage factors for the further math calculations of the different parameters of the quantitative lithostratigraphy.
Keywords: well core photogrammetry; rock color parameter; geological cross section color diagram